2003
DOI: 10.1007/s00167-003-0359-6
|View full text |Cite
|
Sign up to set email alerts
|

Failure strength of bioabsorbable interference screws: effects of in vivo degradation for 12�weeks

Abstract: We investigated the effect of in vivo degradation for 6-12 weeks on the fixation strength of polylactide bioabsorbable interference screws. Ten bioabsorbable interference screws were used to fix the patellar tendon autograft in ten live sheep knees, which were equally divided into two groups and killed in the 6th or 12th week. The control group consisted of four cadaveric knees. Following the killing of the animals the screws were retrieved and reused to fix patellar tendon grafts in cadaveric sheep knees. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
12
0
2
Order By: Relevance
“…They found a dramatic reduction in strength of the complex at both 6 and 12 weeks, mainly due to rupture of the patellar tendon. A significant decrease of the strength of the graft, as reported by Kilicoglu et al [7] and by others [15] in previous animal studies, as a result of graft revascularization or maturation, was not observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…They found a dramatic reduction in strength of the complex at both 6 and 12 weeks, mainly due to rupture of the patellar tendon. A significant decrease of the strength of the graft, as reported by Kilicoglu et al [7] and by others [15] in previous animal studies, as a result of graft revascularization or maturation, was not observed in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…We also speculate that at that time the Sharpey's fibers contributed sig-nificantly to the stability of the implant. On the contrary, using a bioabsorbable interference screw fixation, Kilicoglu et al [7] did not find Sharpey-like fibers at either 6 or 12 weeks; instead, the bone tendon interface was formed of three layers: a superficial band of necrotic cellular debris and active granulation tissue, a middle layer of residual tendon, and the deepest new fibrous tissue formation merging with medullary bone tissue.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, an increase in the fixation strength of PLLA interference screws after intra-articular tenodesis was reported in an experimental study. 11 This increase was not accompanied by an increase in the screw diameter. The authors explained these findings with the observations of Mainil-Varlet et al, who found an acute water uptake by an increase in the crystallinity of the PLLA rods, without an increase in rod diameter.…”
Section: Discussionmentioning
confidence: 94%